The Effectiveness of Domino Card Media on Mathematics Learning Outcomes on Equivalent Fraction Material in Elementary Schools - Etna Liana; Ahmad A. Khozim; Muhammad Iqbal Al Ghozali (PT. Pusmedia Group Indonesia, 2023)
The use of traditional methods, the absence of learning media, students' boredom because they think mathematics is too difficult, and low student learning outcomes in equivalent fraction material are the problems underlying this research. This fact is motivated by the fact that the learning process is still focused on the teacher and not the students. The aim of this research is to find out whether the domino card media at SD Negeri 2 Durajaya, Greged District, Cirebon Regency can improve mathematics learning outcomes regarding equivalent fractions. This research uses quantitative experimental research, Pre-Experiment Design, One-Group Pre-Test Post-Test Design. The instrument for testing used in this data collection method uses test questions. The data collection sample technique used Simple Random Sampling to select 33 class III students at SD Negeri 2 Durajaya, Greged District, Cirebon Regency as the population. Non-parametric statistics with prerequisite tests for normality, homogeneity, and hypothesis testing using the Wilcoxon test to analyze the collected research data. Class III mathematics students at SD Negeri 2 DURAJAYA, Greged District, Cirebon Regency obtained an average pretest score of 75.4545 which was said to be a satisfactory order before using the Mathematics Domino Card media. After using the Mathematics Domino Card media, class III students at SD Negeri 2 DURAJAYA, Greged District, Cirebon Regency obtained an average post-test score of 92.4242 which was categorized as worthy of classification. The Sig (2-tailed) value is 0.000 which is smaller than 0.05, resulting from the Paired Sample test table or T-Test above. In Class III of SD Negeri 2 DURAJAYA, Greged District, Cirebon Regency, it was shown that Ha was approved, this shows that there was a high difference in student learning outcomes before and after the implementation of Domino Card Media. Therefore, it can be assumed that the Mathematics Domino Card Media can provide Effective Mathematics Learning Outcomes for Equivalent Fraction Material at SD NEGERI 2 DURAJAYA Cirebon